Dampak Pemanfaatan Teknologi Business Intelligence untuk Optimalisasi Strategi Penjualan dengan Metode OLAP di Warmindo X - Setyawan, Adhita Arif; Darmawan, Eki Dudi; Adji, Widwi Handari (Journal of Practical Computer Science, 2025)
This research was conducted simulatively on an MSME business called Warmindo X which was used as a case study to test the application of OLAP in a Business Intelligence system. The purpose of this research is to develop a data warehouse and information dashboard system based on Tableau technology, by utilizing the utilizing the OLAP method to support strategic decision making and increase sales effectiveness at Warmindo X. improve sales effectiveness at Warmindo X. BI implementation implementation is carried out using Pentaho Data Integration for the ETL (Extract, Transform, Load) and Tableau for dashboard visualization. The ETL process is used to collect, process, and integrate sales data obtained from the Point of Sales (POS) system. obtained from the Point of Sales (POS) system in Excel format. The data is data is then processed into the data warehouse using a star schema that makes it easier to process the data. (star schema) which facilitates multidimensional analysis. Through the OLAP method, sales data sales data is analyzed based on various dimensions such as product, time, and sales. The results of data visualization in the form of dashboards allow Warmindo to quickly monitor sales performance and make more effective decisions. decisions more effectively. The dashboard provides information on best-selling products, product categories, and sales trends over time. product categories, and sales trends over time. The results showed that with the implementation of Tableau and OLAP, Warmindo X can improve operational efficiency, accelerate the analysis process, and support decision making to strengthen sales strategy and competitiveness in business